Implementasi Program Baca Tulis Al-Qur'an (BTA) dalam Meningkatkan Kemampuan Baca Al-Qur'an di SMA Negeri 6 Solok Selatan - Yuli Yani Safitri; Al Ikhlas (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
This study aims to determine the planning and implementation of the Koran reading and writing program in improving the ability to read the Koran. This research is a qualitative descriptive research. Informants in this study were school principals, teachers of reading and writing the Koran, and students. with data analysis techniques namely observation, interviews and documentation, while data analysis techniques using data collection namely data reduction, data presentation, and and drawing conclusions and verification. Based on the results of the study, it was found that the planning of the Al-Qur'an reading and writing program in improving the ability to read the Qur'an was carried out by determining learning objectives, selecting learning materials, determining the methods used, and conducting learning evaluations. As well as the implementation of the Koran reading and writing program in improving the ability to read the Koran through three stages, namely the first preliminary activity, in this activity the teacher usually prays before learning. The two core activities, in this activity the teacher usually carries out according to the learning steps with the method used. And the third closing activity, in this activity the teacher usually evaluates and reinforces.